COMPARATIVE SUPERSYNTACTIC INTEGRITY IN THE UZBEK AND ENGLISH LANGUAGES. - Dadabayeva, Shirin (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The relation of comparison is a category of a universal nature in languages, which is expressed at all levels of language, including the text. The fact that the textual unity of this relationship comes through supersyntactic integrity (SSB) is a uniquely complex process that needs to be studied. In linguistics, there are opinions about the existence of semantic types of text, among which very few scholars have expressed their views on the expression of the relation of comparison through the text unit. They dwell on comparative texts with the meaning similarity in general way. Therefore, this article analyzes the comparative SSI with the meaning contrast, its type of SSBs representing the comparative relation and identifies their specific features.